Medicamentos altamente diluídos promovem regulação imunológica e efeito protetor na fisiopatologia de camundongos infectados por Trypanosoma cruzi - Temporini, Gislaine Janaina Falkowski (2017)
The aim of this study was to evaluate the effects of different medications diluted above the Avogadro constant in mice infected with Trypanosoma cruzi in the Laboratory of Chagas Disease of the Universidade Estadual de Maringá, Paraná. In a blind, controlled and randomized assay, 84 Swiss male mice, 8 weeks old, IP infected, (1400 trypomastigotes of Y strain-T.cruzi) were allocated into 8 groups: GCaus - Group treated with Kalium causticum 13c (n=10), GCon - Group treated with Conium maculatum 13c (n=11), GLy - Group treated with Lycopodium clavatum 13c (n=10), GCIC Group treated with vehicle for preparation of constitutional medications (7% hydroalcoholic solution) (n=11), GLB - treated with L. clavatum and organotherapic of spleen 13c (n=10), GLC - treated with L. clavatum and organotherapic of heart 13c (n=10), GLBC - treated with L. clavatum, organotherapic of spleen and heart 13c (n=11) and GCICO - treated with vehicle for preparation (7% hydroalcoholic solution) of constitutional and organotherapic medications (n=11).The medications were prepared according to the Farmacopéia Homeopática Brasileira. Treatment with L. clavatum was performed 48 hours before and after infection. 96 and 144 hours after inoculation, L. clavatum was offered associated or not associated with organotherapics, according to the pre-selected groups.The medications and their vehicle were sucussioned and offered diluted in water (1mL/100mL) ad libitum, in amber drinking bottle for 16 hours. Parasitological, clinical parameters and survival were evaluated in GCICO, GLB, GLC, GLBC. Immunological parameters of cytokines, megakaryocytes, Kupffer cells, apoptosis, clinical parameters and survival were evaluated in GCIC, GCaus, GCon, GLy. The GLy group, compared with GCIC, had predominance of Th1 response with TNF-α increase and IL6 decrease, presenting higher survival, less morbidity with higher water consumption, body temperature, higher number of megakaryocytes, Kupffer cells, hepatocytes and splenocytes in apoptosis with a greater number of apoptotic bodies in the liver. The GCon group had increased Th2 response with IL-4 increase, worsening of infection with early mortality of the animals. The GLBC group had a significantly lower peak of parasites and the highest prepatent period compared with GCICO (p<0.05). GLBC and GLB had higher temperature and body weight compared with GCI throughout the infection (p<0.05). However, the increased feed intake was significantly higher only in GLBC compared with GCI at the end of patent period (p<0.05). There was no significant difference in survival of groups GLB, GLC, GLBC compared with GCICO. The results demonstrate that the highly diluted medications are capable of altering the course of murine infection with T. cruzi, promoting a protective effect through alterations of immunological and pathophysiological responses, promoting benefits to the host, opening the way for an alternative approach for the treatment of Chagas disease.